Microbiological characteristics and clinical profile of Stenotrophomonas maltophilia infections in a teaching hospital in northeastern Brazil - João Antonio SOUSA; José Alcântara NETO; Renan Morais SILVA; Cinthya Cavalcante ANDRADE; Leones Fernandes EVANGELISTA; Gleiciane Moreira DANTAS; Maria Carmo TAVARES; Ila Fernanda LIMA; Paulo César SOUSA; Alene Barros OLIVEIRA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: This study aimed to elucidate the microbiological and clinical characteristics of patients affected by infection caused by S.maltophilia in a tertiary hospital in the north-east of Brazil. Methodology: The study consisted of a retrospective analysis of microbiological samples from January 2022 to September 2023 from the microbiology department of the Walter Cantídio University Hospital, Fortaleza, Ceará. The prevalence of these infections was determined, along with the epidemiology and antimicrobial sensitivity profile to sulphamethoxazole/trimethoprim (SMX-TMP) and levofloxacin. Clinical characteristics of the affected patients were identified, such as the use of mechanical ventilation (MV), hemodialysis (HD), previous use of antimicrobials and the outcome of these patients. Results: The prevalence of S.maltophilia infections was 1.79% in the period (35 positive samples and 26 affected patients). Of the positive clinical isolates, there was a predominance from the respiratory tract, with 23 samples (61.43%) from tracheal aspirates and 5 samples from bronchoalveolar lavage (14.57%). The highest number of positive samples was identified in the clinical ICU (23 isolates). About SMX-TMP, 65.71% of the strains were sensitive to increased exposure, 5.71% were fully sensitive and 28.57% were resistant. A profile of strains predominantly sensitive to levofloxacin was observed (91.49%), with 5.71% of the isolates proving sensitive by increasing exposure and 2.85% proving resistant. Women were more affected (57.69%). The average age was 54.33 years. Patients undergoing HD during the infection accounted for 53.84% of the profile obtained, while the use of MV occurred in around 69.23% of those infected. All patients had previously used antimicrobials. 19 patients (69.23%) died and only 7 were discharged from hospital (30.76%). Conclusion: With the findings, it was possible to determine a predominant profile of critically ill patients, with greater involvement of the respiratory tract. We also identified considerable rates of resistance to SMX-TMP, as well as an association between S. maltophilia infection and death.